Calidad de servicio percibida por los clientes de la empresa de transportes y servicios Doam, Iquitos 2022 - Chavez Noriega, Carlos Jesus (2023)
The objective of this study is to determine how well the clients of the transport and services company Doam E.I.R.L., Iquitos, 2022 feel that their experience was; The type of research with a quantitative and descriptive approach was used, with a non-experimental cross-sectional design, the population made up of 20 clients of the transport and services company Doam. The survey was carried out on the 20 clients of the company, and the findings showed that the reliability coefficient of Cronbach's Alpha is equal to 0.877, on the scale for the reliability coefficient, for variable 1: Quality of service. The data indicates that, based on the calculated average of respondents' responses to Variable 1 Service Quality, 13 respondents, or 65.0 percent, believe the company's level of customer service is poor. However, Dimension 5: Empathy of variable 1 Quality of service is located in the "Medium" category with a total of 60.0 percent, as shown in Table N° 13 of the data.